Mitochondrial function meets oncology: the multifaceted role of TFAM across cancer types - Jie Wang; Ruicheng Wu; Fanglin Shao; Zhouting Tuo; Xinrui Li; Koo Han Yoo; Wuran Wei; Zhipeng Wang; Dengxiong Li; Dechao Feng (Apoptosis, 2026)
Mitochondrial transcription factor A (TFAM) is indispensable for mitochondrial DNA (mtDNA) maintenance and transcription, governing cellular bioenergetics. Despite its known physiological importance, TFAM plays a complex and often paradoxical role in cancer biology. This study integrates pan-cancer bioinformatics analyses with experimental evidence to comprehensively elucidate TFAM’s multifaceted impact on tumorigenesis. We systematically investigated the heterogeneity of TFAM across diverse cancer types, specifically focusing on its regulatory mechanisms in metabolic reprogramming, signal transduction, and immune microenvironment remodeling. Our analysis reveals that TFAM functions as a critical node connecting mitochondrial integrity to tumor progression, balancing tumor-promoting and tumor-suppressive roles depending on the context. Finally, we discuss the challenges of targeting TFAM, such as off-target toxicity, and highlight emerging precision oncology strategies, including mitochondria-targeted delivery systems, that aim to exploit these mitochondrial vulnerabilities. Graphical abstract